Preservation and Protection of Cultural Heritage through Digital Security System - Simeonova, Neli; Belovski, Ivaylo; Torlakov, Georgi (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2019)
The preservation and protection of cultural heritage is of special importance nowadays. With the development of technologies, violation methods became more sophisticated. This requires taking stronger security measures for protection of museum items. The aim of the present paper is to present a design of digital security system for museum exhibits based on a microcontroller combined with sensors of different functions and principles of operation.
Keywords: Sensor Systems; Museum Security; Exhibits Protection